Frailty and Activities of Daily Living in Older Adults in Primary Care: A Cross-Sectional Study - Adadıoğlu, Öznur; Seven, Ahmet; Danç, Esin (Makara Journal of Health Research, 2026)
Background: This study aimed to examine frailty status and activities of daily living among older adults. Methods: This descriptive and cross-sectional study was conducted with 306 voluntary participants aged 65 years and older who were registered at a primary healthcare center in a city in Türkiye. Data were collected using the Participant Information Form, the FRAIL Scale, and the Katz Index of Activities of Daily Living. Results: Among the participants, 36.9% were non-frail, 42.2% were pre-frail, and 20.9% were frail. The mean Katz Index score was 5.42 ± 1.35. The mean scores of activities of daily living were 5.97 ± 0.16 in the non-frail group, 5.67 ± 0.74 in the pre-frail group, and 3.95 ± 2.19 in the frail group. Conclusions: Increasing frailty was associated with a decline in the ability of older adults to perform activities of daily living. These findings highlight the importance of early frailty screening in primary care to prevent functional decline and loss of independence.